Generalized elastic flow rerouting scheme. Issue 4 (13th October 2015) - Fouquet, Yoann; Nace, Dritan; Pióro, Michał; Poss, Michael; Żotkiewicz, Mateusz
Abstract : The present study deals with Elastic Flow Rerouting (EFR)—an original traffic restoration strategy for protecting traffic flows in communication networks (including wireless networks) against multiple link failures. EFR aims at alleviating the trade‐off between practicability of traffic restoration and the cost of network resources observed in existing networking solutions. We present an extension of EFR capable of managing multiple partial link failures. We describe EFR and its extension, formulate the EFR related optimization problems, and discuss approaches for their resolution. We also discuss numerical results illustrating effectiveness of EFR in terms of the link capacity cost. © 2015 Wiley Periodicals, Inc. NETWORKS, Vol. 66(4), 267–281 2015